Study of Bacterial Pathogens in Urinary Tract Infection and their Antimicrobial Sensitivity Pattern - Parveen, Rezina; Rahim, Ina (Bangladesh Journal of Infectious Diseases, 2018)
Background: Urinary tract infection (UTI) is one of the most common bacterial infections in Bangladesh. Antimicrobial agents are used for its treatment. The increase in antibiotic resistance among uropathogens is a global problem. Objective: This study was designed to find out the prevalence of UTI, its causative agents and their antimicrobial susceptibility patterns among suspected patients of UTI attending Dhaka Dental College Hospital, Dhaka. Methodology: This cross-sectional study was carried out in Dhaka Dental College Hospital, Dhaka during the period of November 2014 to May 2017. Clinically diagnosed cases of UTI irrespective of age and sex from out-patient department and in-patient department were selected for the purpose of the study. For culture, the urine samples were inoculated on 5% sheep blood agar and MacConkey’s agar media using calibrated loop following standard bacteriological technique. After the incubation period, the plate were examined for bacterial pathogen. The disk diffusion method (Kirby Bauer’s) was used to determine the antimicrobial susceptibility of isolates. Standard inoculums were inoculated on Mueller-Hinton agar and incubated at 37oC for 24 hours. Result: Ninety three urine samples were studied. Among the 93 samples most of them were in the age group of 21 to 30 years. Out of 93 samples, 26 (27.95%) samples were found culture positive. Escherichia coli (92.30%) was found to be the predominant organism. Regarding antimicrobial sensitivity pattern Esch. coli was found to be most sensitive to Imipenem (100%), Amikacin (87.5%), and Nitrofurantoin (83.33%). Conclusion: In conclusion young aged female are commonly suffering from UTI and Escherichia coli is the most common isolated bacteria. Bangladesh Journal of Infectious Diseases, December 2017;4(2):40-44